2024
DOI: 10.3390/ma17030766
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Lanthanum-Modified Tea Waste Biochar and Its Adsorption Performance on Fluoride in Water

Wei Li,
Pengcheng Xie,
Haiyang Zhou
et al.

Abstract: In this study, tea waste was used as a raw material, and TBC (tea waste biochar) was prepared by pyrolysis at 700 °C. La(NO3)3·6H2O was used as the modifier to optimize one-way modification; the orthogonal experiment was undertaken to determine the optimal preparation conditions; and La-TBC (lanthanum-modified biochar) was obtained. The key factors for the adsorption of fluoride by La-TBC were investigated by means of batch adsorption experiments, and kinetics and isothermal adsorption experiments were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Igwegbe et al found that the adsorption efficiency of wheat straw biochar for nitrogen (N) in ammonium chloride solution (NH 4 Cl) reached 95.08%, and the removal of N from landfill leachate by wheat straw biochar was 26.67 mg·g −1 [ 23 ]. Li et al prepared biochar from tea waste at 700 °C and found that biochar was effective in adsorbing fluoride from aqueous solutions, with removal rates of more than 95% from the actual geothermal hot spring water [ 24 ]. Therefore, the adsorption properties of biochar made from different raw materials are different, so it is necessary to study the adsorption effect of different biochars.…”
Section: Introductionmentioning
confidence: 99%
“…Igwegbe et al found that the adsorption efficiency of wheat straw biochar for nitrogen (N) in ammonium chloride solution (NH 4 Cl) reached 95.08%, and the removal of N from landfill leachate by wheat straw biochar was 26.67 mg·g −1 [ 23 ]. Li et al prepared biochar from tea waste at 700 °C and found that biochar was effective in adsorbing fluoride from aqueous solutions, with removal rates of more than 95% from the actual geothermal hot spring water [ 24 ]. Therefore, the adsorption properties of biochar made from different raw materials are different, so it is necessary to study the adsorption effect of different biochars.…”
Section: Introductionmentioning
confidence: 99%